Predictions of Thermo‐Mechanical Properties of Cross‐Linked Polyacrylamide Hydrogels Using Molecular Simulations. Issue 3 (4th January 2019) - An, Meng; Demir, Baris; Wan, Xiao; Meng, Han; Yang, Nuo; Walsh, Tiffany R.
Abstract: Hydrophilic acrylamide‐based hydrogels are emerging platforms for numerous applications, but the resources to fully exploit these materials are currently limited. A deep understanding of the molecular‐level structure/property relationships in hydrogels is crucial to progressing these efforts. Such relationships can be challenging to elucidate on the basis of experimental data alone. Here, molecular simulations are used as a complementary strategy to reveal the molecular‐level phenomena that govern the thermo‐mechanical properties of hydrogels. The focus is on acrylamide‐based hydrogels cross‐linked with N, N ′‐methylenebisacrylamide, generated using previously established computational cross‐linking procedure. The water content is found to be a key determinant in the elastic response of these hydrogels, with enhanced tensile and shear properties at low water content. However, it is also found that increasing water content enhances the hydrogel's thermal conductivity, with the dominant contribution arising from the non‐bonded contributions to the heat flux. In addition, chemical cross‐linking improves the heat transfer properties of the hydrogel, whereas a reduction in convective heat transfer is predicted with an increase in hydrogel cross‐linking. These simulations provide a rational basis for designing and testing customized hydrogel formulations for maximizing both thermal conductivity and mechanical properties. Abstract : Hydrogels are emerging flexible platforms for various applications . Molecular‐level structure/property relationships of hydrogels need to be established to fully exploit these materials. Here, molecular simulations are used as a complementary strategy to reveal the molecular‐level phenomena that govern the thermo‐mechanical properties of hydrogels.